Magnetic and Luminescent Properties of Isostructural 2D Coordination Polymers Based on 2-Pyrimidinecarboxylate and Lanthanide Ions - Amalia García-García; Andoni Zabala-Lekuona; Ainhoa Goñi-Cárdenas; Javier Cepeda; José M. Seco; Alfonso Salinas-Castillo; Duane Choquesillo-Lazarte; Antonio Rodríguez-Diéguez (Crystals, 2020)
A couple of isostructural coordination polymers with the general formula [Ln4(pymca)4(AcO)8]n have been obtained from reactions between pyrimidine-2-carboxylate (pymca) ligand and rare-earth ions (Ln = Dy (1), Nd (2)). These two-dimensional compounds have been characterized and the crystal structures have been solved by single-crystal X-ray diffraction technique, resulting in layers along the bc plane based on pymca and acetate anions that act as bridging ligands between metal atoms. Given that pymca and acetate anions possess carboxylate and hetero-nitrogen groups, it is possible to build a coordination polymer whose metal centers have a nine coordination. Furthermore, static and dynamic magnetic measurements of compound 1 reveal the lack of single molecule-magnet (SMM) behavior in this system due to the following two effects: (i) the ligand field does not stabilize magnetic ground states well separated from excited states, and (ii) anisotropy axes are not collinear, according to results with Magellan software. On another level, luminescent properties of compounds 1 and 2 are attributed to singlet π-π* transitions centered on pymca ligand as corroborated by time-dependent density functional theory (TD-DFT) calculations.